2004
DOI: 10.1590/s1806-37132004000200008
|View full text |Cite
|
Sign up to set email alerts
|

Teste de caminhada de seis minutos: estudo do efeito do aprendizado em portadores de doença pulmonar obstrutiva crônica

Abstract: INTRODUÇÃO: Testes de caminhada de seis minutos vêm sendo utilizados de forma crescente para avaliar a efetividade de diferentes opções terapêuticas clínicas e cirúrgicas em pneumopatias. Entretanto, a falta de padronização para a sua realização pode influenciar as aferições, prejudicando a qualidade da avaliação. Nesse sentido, formulamos a hipótese de que os pacientes têm melhor performance com a realização do teste de caminhada de seis minutos após aprendizado. OBJETIVO: Determinar o possível efeito do apre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
2
14
1
11
Order By: Relevance
“…However, to ensure that tests are reproducible, the walked distance in the second test should not be greater than 10% when compared with the first test, otherwise it is necessary to perform a third test for the appropriate reproducibility of the results 9 . In the present study, the two tests carried out in each one of the corridors were reproducible because the difference between the walked distances was lower than the values identified in the literature 4,9,24,25 . The second test performed in both corridors had a better performance, therefore it was chosen for analysis and comparison of the different lengths.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, to ensure that tests are reproducible, the walked distance in the second test should not be greater than 10% when compared with the first test, otherwise it is necessary to perform a third test for the appropriate reproducibility of the results 9 . In the present study, the two tests carried out in each one of the corridors were reproducible because the difference between the walked distances was lower than the values identified in the literature 4,9,24,25 . The second test performed in both corridors had a better performance, therefore it was chosen for analysis and comparison of the different lengths.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have demonstrated that this learning effect can be identified through the increase in the walked distance when two or more tests are performed, mostly due to the control of anxiety, recognition of the limits of the test and neuromuscular adaptation to the activity 4,24,25 . However, to ensure that tests are reproducible, the walked distance in the second test should not be greater than 10% when compared with the first test, otherwise it is necessary to perform a third test for the appropriate reproducibility of the results 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It presents easy to use, and it is inexpensive. Even as a submaximal exercise test it can identify patients with poor prognosis and help in making the most appropriate therapeutic measures [7,8].…”
mentioning
confidence: 99%
“…Sabe-se que em diversos testes de esforço o efeito aprendizado pode melhorar o rendimento do indiví-duo 2,15,16 , daí a importância da randomização. Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] .…”
Section: Resultsunclassified
“…Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] . Na padronização do TC6, houve preocupação com a utilização do estímulo verbal 2 , motivado por estudos que mostraram que o estímulo verbal pode aumentar a distância percorrida em até 30 metros 3,4 e assegura máxima motivação e performance do indivíduo 2,18,19 .…”
Section: Resultsunclassified